Lessons from COURAGE - Sylvester, Bruce (MD Conference Express, 2008)
The Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation [COURAGE] trial evaluated percutaneous coronary intervention (PCI) as an initial management strategy in patients with stable coronary artery disease. Patients were randomly assigned to treatment with PCI in addition to medical therapy (n=1149) or medical therapy alone (n=1138). In the primary analysis, PCI did not reduce the risk of death or nonfatal myocardial infarction [Boden WE et al. N Engl J Med 2007].